Sistem Informasi Pemantauan Pasien Postpartum Pasca Pulang Rumah Sakit : Tinjauan Literatur - Ahmad Safril Annur; Saiful Bukhori; Muhammad Ihwan Narwanto (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Maternal Mortality Rate (MMR) in Indonesia remains high, particularly during the postpartum period, which accounts for the majority of maternal deaths. Jember Regency is among the regions with the highest MMR in East Java, with many fatalities occurring after mothers are discharged from the hospital. Suboptimal coordination between hospitals and primary health centers, limited clinical data exchange, and delayed early detection of danger signs highlight the need for an integrated information system to support continuous postpartum monitoring. This study aims to identify concepts, models, and empirical findings related to postpartum monitoring information systems through a literature review. Articles were retrieved from Google Scholar, PubMed, and ScienceDirect using keyword combinations of â€œinformation system,â€ â€œmonitoring,â€ and â€œpostpartum,â€ limited to publications from 2020â€“2025. The findings show that community-based digital accompaniment models such as SMAP CARE effectively enhance early detection of complications. Similarly, JagaBunda provides a structured and proactive risk-screening framework applicable to postpartum conditions. Moreover, integrating monitoring data with electronic maternal and child health reporting systems is essential to ensure accuracy and timely clinical response. Overall, the literature confirms that an effective postpartum monitoring information system must incorporate digital accompaniment, proactive risk assessment, and integrated data management across healthcare levels.